Goals and Objectives of the Export-Import Operations Account - А, Misirov; B, Eshpulatova Z.; Sh, Usmanov Sh. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article reveals the goals and objectives of the export-import transaction account, solutions to the problem, changes and regulations in the export-import sphere in our country today, and gives conclusions and suggestions within the framework of the topic.